QUALITY OF LIFE IMPROVEMENT OF CHRONIC HEART FAILURE PATIENTS AFTER THE EFFECT ENHANCED EXTERNAL COUNTERPULSATION (EECP) THERAPY - Starry Homenta Rampengan; Anita Dundu; Joedo Prihartono; Suzanna Immanuel; Minarma Siagian (Journal of Global Pharma Technology, 2017)
Objective: This study aimed to evaluate the risk factor of depression level before and after EECP therapy in chronic heart failure (CHF) patients. Methods: We performed a double-blind random clinical trial between January 2014 and June 2015 in 99 patients with CHF who had received EECP therapy at Jade Cardiovascular Clinic, Manado, North Sulawesi, Indonesia. The CHF patients were categorized into 2 groups, i.e. 49 patients had sham EECP therapy and 50 patients had EECP therapy. The patients filled WHO-5 questionnaire before and after receiving EECP therapy. Statistical analysis was performed for all output, either for primary, secondary or safety output. Results: The baseline characteristics of both groups have no significant difference. We found no significant difference of WHO-5 questionnaire result in sham before and after EECP therapy, but in EECP group showed statistically significant difference (p<0.05). WHO-5 questionnaire attributes result were found significantly improvement of felt cheerful and good spirit (p=0.03) and woke up feeling fresh (p=0.030) in EECP group compared with sham group. Conclusion: EECP therapy was effective to reduce depression so that improve quality of life in CHF patients.Keywords - chronic heart failure, enhanced external counterpulsation therapy, quality of life, world health organization